PENINGKATAN KETERAMPILAN MENGIDENTIFIKASI UNSUR INTRINSIK CERPEN MENGGUNAKAN MODEL KOOPERATIF TIPEPAIR CHECK - Garagasi, Albedhmake Vandaras; Priyadi, A. Totok; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractA general problem in this research is how the improvement of identifying the intrinsic elements skills of short story using the cooperative model type of Pair Check at the students of XI IPS SMA WidyaPratama, Kecamatan Sungai Raya, KabupatenKubu Raya?". This was a researcher?s effort to improve the identifying  the intrinsic elements skills of short story of students and provided a new variation in learning process as well as resolving students? learning difficulties in in increasing the students? score.This research used qualitative descriptive method form. The procedures in this research was a classroom action research (CAR) by four stages, there are action planning (planning), implementation of the action (action), observations (observation), and reflection (reflecting).Based on the results of data analysis in this research was known that the application of  identifying the intrinsic elements of short story by using the cooperative learning model type of  pair check can improve student learning outcomes. After done with the action I  students? average was  69,75 with the highest score was 89, action II with the students? average score was 74,33 with average score was 89, and the action III, students? average score was 83.33%with the highest score was 89.Keywords: Improvement, Model, Cooperative, Pair Check.